Waralaba Franchiese di Indonesia - Adelina Murti Syafiina; Rusnandari Retno Cahyani (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2024)
Franchise is a form of business partnership in which the owner of a brand or business concept (franchisor) gives permission to another party (franchisee) to use and manage their business in accordance with predetermined guidelines. This involves exchanging the right to pay initial fees, royalties, or other fees or special rights owned by individuals or business entities to a business system with business characteristics in order to market goods or services that have proven successful and can be utilized or used by other parties. based on a franchise agreement. A franchise must have a legal basis which is part of the agreement or contract. To avoid undesirable things, before being bound by a franchise agreement, each party involved must pay attention to each point in the franchise agreement carefully and thoroughly. Therefore, the franchise agreement is a very important part of the franchise business.